ANALISIS PERMINTAAN UANG KUASI DI INDONESIA PERIODE 2000-2014 - Putro, Tri Sukirno; Mayes, Anthony (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
US $ and 3-month deposit rate of the quasi money demand in Indonesia period 2000-2014.This study uses annual time series data obtained from the Central Bureau of Statistics, Economic and Financial Statistics Indonesia and Bank Indonesia. The analysis model used in this study is motode Multiple Linear Regression with SPSS version 22. From the results of tests performed with Simultaneous Regression Test (Test F) indicate that significant value 0.000> 0.05, which means jointly variables gross domestic product, exchange rates (exchange rate) and the 3-month deposit rates affect the demand for the number of quasi-money in Indonesia the period 2000-2014. Partial Regression Test (Test t) produces t value of gross domestic product> 14 314 t table> 2,262 gross domestic product, which means a positive effect on demand for quasi-money. Exchange rate variable yield amounted to 1,611 t value <2.262, which means, the rupiah positive effect on the demand for quasi-money in Indonesia. Variable 3-month deposit rate has a value t is smaller than t table is 0.790 <2.262 means that the deposit rate 3-month positive effect on the demand for quasi-money in Indonesia. The magnitude of the effect caused by the value (R2) is 0.981, which means that jointly gross domestic product, exchange rates and 3-month deposit rate affects the demand for quasi-money in Indonesia amounted to 98.1% while the remaining 1.9% is affected by the other variables not examined in this study.Keywords: Gross Domestic Product, Exchange, Deposit Interest and Money Quasi 3 months.